Is Primary Aldosteronism Still Largely Unrecognized? - Buffolo, Fabrizio; Monticone, Silvia; Burrello, Jacopo; Tetti, Martina; Veglio, Franco; Williams, Tracy Ann; Mulatero, Paolo (Hormone and Metabolic Research, 2017)
Primary aldosteronism (PA) was first reported by Jerome W. Conn in 1954 when it was considered a rare disorder, only suspected in cases of hypertension and spontaneous hypokalemia. Over the last 30 years, with the wide application of the plasma aldosterone to plasma renin activity ratio as screening test, the clinical spectrum of PA has dramatically changed. Different studies displayed significant differences in term of patients investigated, diagnostic criteria and hormonal assays; however, large prospective studies with robust diagnostic criteria indicated that the prevalence of PA is around 6% of the general hypertensive population and 11% of the patients referred to hypertension centers. In light of these epidemiological studies, the Endocrine Society Guideline recommends the screening for PA of around 50% of patients with hypertension, and identifies the categories of patients at high risk for the disease. However, clinical data obtained from “real-life” show that the screening rate is much lower and PA remains an under-diagnosed and under-treated cause of secondary hypertension with an associated increased risk of cardio- and cerebrovascular mortality and morbidity.
Keywords: aldosterone; primary aldosteronism; aldosterone producing adenoma; bilateral adrenal hyperplasia